Tinjauan Penggunaan Berita Acara Laboratories Kriminal Sebagai Bukti Surat Dalam Perkara Narkotika - Satya Dipa Asriga (Sebelas Maret University, 2019)
This research has something as a purpose to show how deep the using of instrument of evident is. It is works properly as Criminal Procedural Law or not. Not only for the based of judgement but also for the based of defnite the matter of narcotics criminalism. The research is one of normative law research which has two kind of side view, applied knowledge and a perspective with case approach. Primary law material and secondary law material are used for reach this research and collected by literature study. The conclusion based on the result of study and research is: offcial report of criminal laboratories is appropriate with stipulation of article 187 letter C Criminal Procedural Law, because it has just fullfl the qualifcation as legal evident letter.The matter about dualism of criminal laboratories, it has been described by named this instrument of evident are free and not arouse effect on the power of authentication appraisal. The second matter, letter evident as the research of criminal laboratories offcial report in the decision of narcotics case was not the only point on decision judgement, but judges who look out this case has to be flled by minimum autenthication azaz. It’s showed by at least two things of legal evidents instrument, and the law is appropriate with negative authentication system which is not has the same meaning as a perfect instrument of evident. The underlined words here, the judges is free to make a point about the power and the rightness of evident’s instrument.Keyword : criminal laboratories offcial report, letter evidence, narcotics